Circular RNAs in ferroptosis: regulation mechanism and potential clinical application in disease - Li, Fei; Li, Pei-Feng; Hao, Xiao-Dan (Frontiers in Pharmacology, 2023)
Ferroptosis, as an iron-dependent non-apoptotic form of cell death, was reported to be involved in the pathological process of a variety of diseases, especially tumor occurrence, organ injuries, and degenerative pathologies. Several signaling pathways, including polyunsaturated fatty acid peroxidation, glutathione/glutathione peroxidase 4, cysteine/glutamate antiporter system (system Xc-), ferroptosis suppressor protein 1/ubiquinone, and iron metabolism, etc. were involved in the regulation of cell ferroptosis. Circular RNAs (circRNAs), which are with a stable circular structure, are considered to have great potential in the diagnosis and treatment of diseases. Increasing evidence suggested that circRNAs play an important regulatory role in the progression of many diseases via the ferroptosis pathways. Ferroptosis-inhibitory and ferroptosis-stimulating circular RNAs have great potential to become novel diagnostic markers or therapeutic targets for cancers, infarctions, injuries, and diabetes complications linked to cell-ferroptosis. In this review, we seek to summarize the role of circular RNAs in the molecular mechanisms and regulatory networks of ferroptosis and their potential clinical applications in ferroptosis-related diseases. This review will help us to understand the roles of ferroptosis-related circRNAs and provides new perspectives for the regulation of ferroptosis, and new directions for the diagnosis, treatment, and prognosis of the related diseases.